The effect of monofluorophosphate implant in white rat mothers towards the level of fluor in the incisors of their young babies (Rattus-rattus) - Widjijono Widjijono (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Fluoride has been widely used in the prevention of dental caries for a long time. To prevent dental caries, fluoride must be induced in low amount at high frequency. Inducing it through implantation process even make slow release of small concentration of fluoride. Purpose: The aim of this research was to analyze whether the induction of monofluorophosphate (MFP) implant into the white rat mothers affects the level of fluoride in the incisors of their young babies. Method: The objects of the research were twenty white rat mothers in two days of pregnancy which then were divided into four groups (n=5). First, those mothers have been induced with implant under their back skin until their born young babies in the age of 35 days (n=5). The level of fluoride in the incisors of those young babies then is measured with Potentiometer. The obtained data were finally analyzed with One-Way ANOVA test and continued by with LSD test (p=0.05). Result: The result of this research showed that the means of the fluoride level in the incisors of those babies divided into those four groups in series were about 11956.16±201.35 ppb (K), 27328.04±234.56 ppb (P1), 37267.21±248.86 ppb (P2), and 18103.50±267.11 ppb (P3). The result of ANOVA test then showed that the induction of various MFP implant levels significantly affected the level of fluoride in the incisors of the babies. The mean differences among the treatment groups after being tested with LSD 0.05 were also significant. Conclusion: The finding confirm that the significant increasing of the optimal fluoride retention in the incisors of white rat babies can be achieved with the induction of fluoride with MFP ions implant in about 52.98 mg.Latar belakang: Pencegahan karies gigi menggunakan senyawa fluor telah banyak dilakukan dan berlangsung dalam jangka waktu lama. Pemberian fluor dalam jumlah rendah dan frekuensi tinggi merupakan pemenuhan kebutuhan pencegahan karies gigi. Pemberian dengan cara implantasi memberikan keluaran fluor jumlah kecil dan waktu lama. Tujuan: Penelitian ini bertujuan untuk mengetahui apakah induk tikus yang diberi implan-MFP berpengaruh terhadap kandungan fluor gigiseri anak tikus. Metode: Subjek penelitian adalah 20 ekor induk tikus putih bunting 2 hari dibagi 4 kelompok (n=5). Induk diberi implan pada bawah-kulit punggung hingga anak tikus lahir dan pada umur 35 hari (n=5). Kandungan fluor pada gigi seri anak tikus diukur menggunakan Potensiometer. Data yang diperoleh dianalisis dengan Anova 1 jalur dilanjutkan uji LSD (p=0,05). Hasil: penelitian menunjukkan rerata fluor gigiseri anak tikus berturut-turut sebesar: 11956,16±201,35 ppb (K), 27328,04±234.56 ppb (P1), 37267,21±248.86 ppb (P2), dan 18103,50±267,11 ppb (P3). Hasil: Anava membuktikan bahwa ada pengaruh bermakna akibat variasi kadar MFP dalam implan terhadap kandungan fluor gigi anak tikus. Beda rerata antar kelompok perlakuan diuji dengan LSD0,05 memperlihatkan perbedaan bermakna pada semua kelompok. Kesimpulan: Penelitian dapat disimpulkan bahwa kenaikan secara bermakna terhadap retensi fluor optimal dalam gigiseri tikus putih pada pemberian fluoridasi menggunakan implan dengan muatan MFP: 52,98 mg.